Assessing environmental factors and human practices on the welfare of working donkeys in Kenya - James Mutiiria Kithuka; Timothy Muthui Wachira; Joshua Orungo Onono; Mary N. Gichure (Discover Animals)
Abstract Donkeys play a crucial role in supporting the livelihoods of low-income households in Kenya by providing complementary services in transportation, agriculture, and other economic activities. Their importance not withstanding, working donkeys frequently face poor welfare conditions, often due to mistreatment by owners, limited resources, poor environmental conditions, and a lack of recognition in policy frameworks like the national livestock master plan. Donkeys, due to their shared environment with humans are constantly exposed to welfare challenges, whose extent has not been quantified. This study aimed to assess the role of environmental and human factors on the welfare of working donkeys in Kenya, surveying 1059 donkey owners and their donkeys across 20 out of 47 counties. The Equine Welfare and Owner Behaviour tool, developed based on the Five Domains Model of animal welfare, was used to assess factors related to nutrition, environment, health, behaviour, and mental state. Data were collected through stratified random sampling, with responses from 26 questions in the tool categorized into three areas namely; (1) owner behaviour, practices and livelihood income outcomes, (2) environmental factors and (3) donkey welfare. Robust ethical guidelines ensured respectful and unbiased data collection. Overall, 28% of donkey owners demonstrated positive welfare practices while 72% required improvement, based on the set threshold of 0.85. Owner behaviour and practices scored 0.70 on average, with compassionate handling (0.75) and food quality (0.73) achieving relatively high ratings. Livelihood outcomes, reflecting socio-economic challenges, averaged 0.65, with 79% of owners reporting satisfactory outcomes and 21% requiring improvement. Environmental parameter scores averaged 0.64, with notable challenges in water access (0.59) and shelter provision (0.55), which are essential for sustaining donkey health and welfare. The overall welfare score for donkeys was 0.80, meeting acceptable standards in general health (0.86) and non-lameness (0.90), though ectoparasite presence (0.84) and body lesion occurrence (0.76) highlighted persistent welfare concerns. Improving environmental conditions, enhanced owner practices, and diversified income streams, are essential for better donkey welfare. Results of this study will inform evidence-based interventions aimed at improving the welfare of working donkeys in Kenya.